Genetic diversity of tropical maize inbred lines combining resistance to Striga hermonthica with drought tolerance using SNP markers - Mengesha, W.; Menkir, A.; Unachukwu, N.N.; Meseka, S.K.; Farinola, A.; Girma Tessema, G.; Gedil, Melaku A (Wiley, 2017)
Striga hermonthica and drought are the major stresses limiting maize yields in sub-Saharan Africa. The search for diverse maize lines’ tolerance to drought and resistance to S. hermonthica (DTSTHR) is very crucial for yield improvement in areas affected by the two stresses. Understanding the genetic diversity among the lines is important to develop cultivars resistant to S. hermonthica and tolerant to drought. The lines were developed from biparental crosses of drought-tolerant and Striga-resistant lines. A total of 128 DTSTHR maize lines were characterized using single-nucleotide polymorphism (SNP) markers. Results of the cluster analysis based on 3297 SNP markers showed four distinct groups consistent with the pedigrees of the lines. Furthermore, model-based analysis also formed the same groups of the DTSTHR lines. Integrating the pedigree information with combining ability and the SNP analyses may provide defined heterotic groups for maize improvement work in West and Central Africa. These results also help breeders to utilize DTSTHR lines present at IITA for developing biparental crosses without disrupting the heterotic groups they have established in their breeding programmes.